Proceedings of the 34th Annual Conference on Design Automation Conference - DAC '97 1997
DOI: 10.1145/266021.266275
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel circuit partitioning

Abstract: Abstract-Many previous works in partitioning have used some underlying clustering algorithm to improve performance. As problem sizes reach new levels of complexity, a single application of a clustering algorithm is insufficient to produce excellent solutions. Recent work has illustrated the promise of multilevel approaches. A multilevel partitioning algorithm recursively clusters the instance until its size is smaller than a given threshold, then unclusters the instance while applying a partitioning refinement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
185
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(186 citation statements)
references
References 38 publications
1
185
0
Order By: Relevance
“…The survey by Alpert and Kahng [10] provides a detailed description and comparison of various such schemes. Recently a new class of hypergraph bisection algorithms has been developed [11,23,15,22], that are based upon the multilevel paradigm. In these algorithms, a sequence of successively smaller (coarser) hypergraphs is constructed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey by Alpert and Kahng [10] provides a detailed description and comparison of various such schemes. Recently a new class of hypergraph bisection algorithms has been developed [11,23,15,22], that are based upon the multilevel paradigm. In these algorithms, a sequence of successively smaller (coarser) hypergraphs is constructed.…”
Section: Introductionmentioning
confidence: 99%
“…This bisection is then successively projected to the next level ®ner hypergraph, and at each level an iterative re®ne-ment algorithm (e.g., KL [1] or FM [3]) is used to further improve the bisection. Experiments presented in [23,15,22] have shown that multilevel hypergraph bisection algorithms can produce substantially better partitionings than those produced by non-multilevel schemes. In particular, hMETIS [20], a multilevel hypergraph bisection algorithm based upon the work in [23] has been shown to ®nd substantially better bisections than current state-of-the-art iterative re®nement algorithms for the ISPD98 benchmark set that contains many large circuits [18].…”
Section: Introductionmentioning
confidence: 99%
“…MB*-tree is inspired by the success of the multilevel framework in graph/circuit partitioning such as Chaco [10], hMetis [12], and ML [2], placement such as MPL [4], £ This work was partially supported by the National Science Council of Taiwan by Grant No. NSC-91-2215-E-002-038.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that both PROP and SHRINK-PROP are "flat" partitioners, i.e., they do not use the multilevel paradigm use in many recent partitioners like hMetis [22], ML [3], and LSR/MFFS [8]. The multilevel paradigm is orthogonal to our techniques, and can be used with both PROP and SHRINK-PROP to yield faster and probably better results.…”
Section: B Ispd-98 Benchmarksmentioning
confidence: 99%